Assessing Aquatic Plant Diversity and Management Potential in Wetlands in Northwestern and Southwestern Bangladesh: 10.32526/ennrj/23/20240287 - Hossain, Md. Foysul; Chakroborty, Koushik; Chowdhury, Gazlima; Bhuyain, Sumiya; Hossain, Abrar; Ritu, Mst. Mosfeka Khatun; Jahan, Roksana (Environment and Natural Resources Journal, 2025)
Aquatic plants are essential organisms for assessing ecological health and for managing and conserving aquatic biodiversity. The present study investigated the diversity of aquatic flora, in addition to their applications and management, in northwestern (Gajner Beel) and southwestern (Padma Beel) Bangladesh. This research utilized a mixed-methods approach, incorporating observation of the study area for collecting samples, qualitative interviews, and quantitative surveys. A total of 38 aquatic plant species of 4 types belonging to 16 orders and 23 families were recorded from the two wetlands. Asterales was the predominant order in both wetlands, with Araceae and Asteraceae being the largest families. Almost half (44%) of the aquatic plants in both ecosystems bloomed during the rainy season. In Gajner Beel and Padma Beel, 41% and 48% of aquatic plants, respectively, rarely occurred, while 31% and 41% of aquatic weeds were frequent, respectively. Approximately a quarter of the plants have an unevaluated IUCN conservation status, with about 13% of plants in Gajner Beel and 15% in Padma Beel being exotic. Farmers only employ manual or mechanical techniques to control common aquatic weeds, without any preventive measures. About 74% of the aquatic plants in both regions are used for various purposes by local people, including traditional medicine, human food, animal feed, raw materials for handicrafts, and fertilizers. The study examined management approaches for the aquatic flora in both regions, emphasizing their potential utilization.